Translation of Geographical Realia of the Apocalyptic Novel - Movchan, Maryna (Studia Philologica, 2026)
This article explores the theoretical underpinnings of translating nominative units from the apocalyptic novel, focusing on “realia” and “irrealia” as markers of the fictional world. The study examines the context-dependent nature of these lexical units, their categorization across the thematic group of geographical referents, and the unique challenges they pose in apocalyptic literature translation. The study integrates L. Venuti’s strategies of domestication and foreignization with A. Popovič’s theory of stylistic shifts to address the reconstruction of the fictional world in Ukrainian translations. This article highlights the significance of irrealia as products of the author’s imagination and the necessity of special translation tactics such as intensification and substitution to preserve the genre’s stylistic features and pragmatic potential across cultures. The conclusions of the research demonstrate that the choice of translation strategy and tactics is functionally dependent on the type of nomination.